Pengaruh Corporate Social Responsibility dan Ukuran Perusahaan Terhadap Profitabilitas dan Reputasi Perusahaan Sektor Healthcare di Bursa Efek Indonesia Tahun 2020-2024 - Neina Nadifa Balqis; Eni Wuryani (Jurnal Kendali Akuntansi, 2026)
Changes in the healthcare sector during the 2020–2024 period have increased the pressure on companies not only to improve their financial performance but also to demonstrate social responsibility as a means of building trust and reputation among stakeholders. This study aims to analyze the influence of Corporate Social Responsibility (CSR) and firm size on the profitability and reputation of healthcare companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The study employs a quantitative approach using purposive sampling, resulting in a sample of 7 companies with a total of 31 observations after outlier removal. The data were analyzed using multiple linear regression. The results indicate that Corporate Social Responsibility has a positive effect on profitability, while firm size has a negative effect on profitability. Meanwhile, Corporate Social Responsibility and firm size do not have a significant effect on corporate reputation. These findings suggest that the disclosure of Corporate Social Responsibility is more effective in improving financial performance than in building corporate reputation, whereas the size of a company’s assets has not yet been shown to enhance market perceptions. This study implies that companies need to strategically optimize the implementation and disclosure of Corporate Social Responsibility and enhance other factors beyond company size to strengthen corporate reputation.